(untitled) (Al-Qamar, 2021)
important issues related to civilization and culture in which the arguments of critics of modern trends and their analysis have been analyzed. According to Islam, it is not permissible for a Muslim woman to marry a free woman or a slave in the marriage of a polytheist. Allāma Qurtubī has quoted the consensus of the ummah that "a Muslim woman cannot marry any non-Muslim. It is the result of distance from the religion of understanding, ignorance of the style and methodology of the narrators, because the arguments of the non-believers in this issue are so strong that their denial is not correct The position of the critics on this issue is also in line with the understanding of the Imams and traditional scholars. Similarly, another important issue is whether human nature decides what is halāl and what is harām. To deduce that Nature should be considered as a permanent source of religion in the matter of condition and sanctity is not correct in any way. Is tantamount to inflicting, is obviously misunderstood. And this thing needs to be considered as a permanent source of religion of nature or to occupy the position of dissolution and prohibition of human beings. Even in this case, the position of the critics is correct that the decision of halāl and harām will be decided by the texts of Quran and Sunnah and not human nature will be considered as the source of religion in halal and haram.